Nickel -supported PdM (M = Au and Ag) nanodendrites as formate oxidation (electro)catalytic anodes for direct fuel cells and hydrogen generation at room temperature. Issue 15 (28th March 2023) - Pan, Bowei; Shan, Shuang; Wang, Junpeng; Tang, Quan; Guo, Longfei; Jin, Tao; Wang, Qiao; Li, Zhen; Usman, Muhammad; Chen, Fuyi
Abstract : Palladium–gold (PdAu) and palladium–silver (PdAg) nanodendrites on a nickel foam are bifunctional catalysts for formate oxidation reactions (FORs) and formate dehydrogenation reactions (FDRs). Abstract : The study provides a proof of concept for the first time that unique palladium–gold (PdAu) and palladium–silver (PdAg) nanodendrites are bifunctional catalytic active sites for formate oxidation reactions (FORs) and formate dehydrogenation reactions (FDRs). The unique nanodendritic structure was developed via a simple galvanic displacement reaction for the direct growth of PdAu and PdAg nanodendrites on a nickel foam (PdAu/NiNF and PdAg/NiNF). These PdAu/NiNF and PdAg/NiNF electrodes exhibited 2.32 and 1.59 times higher specific activity than that of the commercial Pd/C electrode and promising stability toward FORs. Moreover, the PdAu/NiNF and PdAg/NiNF nanodendrites were also highly active and selective catalysts for hydrogen generation from a formate solution with turnover frequency (TOF) values of 311 h −1 and 287 h −1 respectively. Impressively, a passive air-breathing formate fuel cell with PdAu/NiNF used as an anode can yield an open-circuit voltage of 1.12 V and a peak power density of 21.7 mW cm −2, which outperforms most others reported in the literature. PdAu and PdAg nanodendritic catalysts supported on a nickel foam demonstrate an open structure and uniform catalyst distribution and offer a promising nanoalloy for air-breathing formate fuel cells and on-site chemical hydrogen production systems.